Estudo de aumento de eficiência e produção de uma caldeira de recuperação química - Silva, Rodrigo Moretto da [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The present work aims to analyze and study the increase in efficiency and production of a chemical recovery boiler to reach the future objectives of increasing the pulp production of the analyzed factory. Project data was obtained for its installation in 1985 and for the renovation project in 2002, besides the collected data during the operation of the boiler between 2015 and 2016. By analyzing the data a discussion about the bottlenecks that hold back the boiler's production took place followed by some modification propositions, from process changes to the use of a new project of a reheat steam cycle boiler. The best solutions were defined by analyzing the efficiency and production increase viability related to the theoretical and local difficulties of the proposals. Part of the solutions considered efficiency and production increase calculations and part was theoretical, since they are projects by third party companies. It was defined that firstly it is necessary to apply maintenance on the current identified bottlenecks so that the following two solutions can be considered. The first, and simpler, is the modification of certain operational parameters of the boiler to reach an increase of the efficiency and production of the plant, while the second, more complex, aims to modernize areas of the furnace and air system to reach a more significant result. It was decided that, considering the main objectives of the factory, the reheat steam cycle boiler does not comply with some of the company's project prerequisites

O presente trabalho tem como foco a análise e estudo do aumento de eficiência e produção de uma caldeira de recuperação química para atingir os objetivos futuros de aumento de produção de celulose da fábrica analisada. Foram obtidos os dados de projeto de implantação de 1985 e do projeto de renovação da caldeira de 2002, além dos dados coletados durante a operação entre 2015 e 2016. Através da análise dos dados foi realizada uma discussão dos gargalos que dificultam a produção da caldeira e em seguida foram propostas modificações diversas, desde mudanças de processos até a utilização de um novo projeto de caldeira com ciclo de reaquecimento de vapor. As melhores soluções foram definidas analisando a viabilidade de realização do aumento de produção em relação às dificuldades locais e teóricas das propostas. Parte das soluções considerou cálculos de aumento de produção e eficiência e parte foi teórica, por serem projetos de empresas fornecedoras externas. Definiu-se que primeiramente será necessário realizar manutenção nas áreas identificadas como gargalos para então realizar duas possíveis soluções. A primeira, mais simples, altera os parâmetros de operação da caldeira alcançando um pequeno aumento de produção e eficiência, enquanto a segunda, mais complexa, visa modernizar partes da fornalha e do sistema de ar para alcançar um aumento de produção mais significativo. Definiu-se que, levando em consideração os objetivos da fábrica, a caldeira com ciclo de reaquecimento de vapor não atende alguns dos pré-requisitos de projeto da empresa
Keywords: Caldeiras; Caldeiras a vapor; Fornalhas; Boilers